[Primary cutaneous leiomyosarcoma revealed by soft tissue tumor recurrence] Léiomyosarcomes cutanés primitifs révélés par une récidive tumorale des tissus mous - Jean-Baptiste Andonaba; Ollo Rolland Some2; Bakary Gustave Sanon; Boukary Diallo (Our Dermatology Online, 2017)
Background: Primary cutaneous leiomyosarcoma (LCP) is a malignant tumor that can originate from smooth muscles (hair arrestor or vessels of hypodermic tissue). Recidivism rates vary by type. We report two particular cases by the volume of their recidivism and to underline the difficulties of management. Observations: ZA, 41 years old, was received after surgery for a voluminous, painless, firm, mobile and ovoid mass of 7 cm on the knee. The tumor occupied mainly the superficial and reticular dermis. It did not have immunohistochemistry but a re-reading of the blade concluded at diagnosis. The assessment of the extension did not objectify anything and the patient lost sight of. KM, 36 years was received 3 months after surgery, under the same conditions for a voluminous ulcerous burgeoning tumor, oblong 9 cm long axis of the shoulder curve. The histopathological lesions were extended to the subcutaneous tissue. The extension report showed lymphadenopathy, hepatic and pulmonary metastases. The patient underwent clean surgery associated with adjuvant chemotherapy. Conclusion: These relapses have no reliable information on the prognostic factors of their initial management. Nevertheless, the major factor of recurrence remains the tumor clearance, probably not obtained during the first excision. Close multidisciplinary collaboration is essential for the appropriate management of LCP.